Asparagus cochinchinensis alleviates disturbances of lipid metabolism and gut microbiota in high-fat diet-induced obesity mice - Luo, Shiyue; Zhou, Lixiao; Jiang, Xuejun; Xia, Yinyin; Huang, Lishuang; Ling, Run; Tang, Shixin; Zou, Zhen; Chen, Chengzhi; Qiu, Jingfu (Frontiers in Pharmacology, 2022)
Asparagus cochinchinensis is a valuable traditional Chinese medicine that has anti-inflammatory ability and effectively regulates the dysbiosis within the body. Obesity is usually characterized by chronic low-grade inflammation with aberrant gut microbiota. However, the role of Asparagus cochinchinensis against obesity remain unknown. Therefore, a high-fat diet (HFD)-induced obese mouse model with or without aqueous extract from Asparagus cochinchinensis root (ACE) treatment was established herein to determine whether ACE alleviates obesity and its involved mechanisms. Our results showed that ACE administration significantly decreased the weight gain and relieved dyslipidemia induced by HFD. Treatment of ACE also improved glucose tolerance and insulin resistance in obese animal model, and remarkably decreased inflammation and lipogenesis in the liver and adipose. Moreover, administration of ACE significantly reshaped the gut microbiota of obese mice. These findings together suggest that ACE has beneficial effect against HFD-induced obesity and will provide valuable insights for the therapeutic potential of ACE against obesity and may aid in strategy-making for weight loss.